POSSESSIVENESS IN THE ENGLISH LANGUAGE - Данилова, В.В.; Каримбаева, А.А. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2014)
The given article is devoted to the problem of possessive case in the English language. The authors identify the types of possessive case as well as the ways of its expression – analytical and synthetical. Practical value of the research consists in comparative analysis of analytical and synthetical types of possessiveness on the basis of modern English prose Elizabeth Gilbert “Eat, Pray, Love”.
Keywords: possessive case; possessiveness; analytical form; synthetical form